SIPHON ZONES IN THE GENUS CORALLIOCHAMA - MULLERRIED, FEDERICO KG (Universidad Nacional Autónoma de Mexico, Instituto de Biología, CD MEXICO, DF, MEX, 1949)
A complete analysis was made of a representative sample of Mexican agar, from Compania Mexicana de Agar, Ensenada, Baja California The values obtained for moisture, ash, sand, silica, ethereal extract, crude fiber and proteins, were simitar to those repo
CIENC MEX
Keywords: SIPHON ZONES, GENUS CORALLIOCHAMA; MULTIDISCIPLINARIA; BIOLOGIA HUMANA; FISIOLOGIA HUMANA